GW150914: First results from the search for binary black hole coalescence with Advanced LIGO - Abbott, B. P.; Davies, G. S.; LIGO Scientific Collaboration and Virgo Collaboration (American Physical Society, 2016)
On September 14, 2015, at 09∶50:45 UTC the two detectors of the Laser Interferometer Gravitational-Wave Observatory (LIGO) simultaneously observed the binary black hole merger GW150914. We report the results of a matched-filter search using relativistic models of compact-object binaries that recovered GW150914 as the most significant event during the coincident observations between the two LIGO detectors from September 12 to October 20, 2015 GW150914 was observed with a matched-filter signal-to-noise ratio of 24 and a false alarm rate estimated to be less than 1 event per 203000 years, equivalent to a significance greater than 5.1 σ